2015
DOI: 10.1007/s00394-015-0948-4
|View full text |Cite
|
Sign up to set email alerts
|

Mediatory effect of circulating vaspin on resting metabolic rate in obese individuals

Abstract: Circulating vaspin level is higher in women than in men in obese individuals. Moreover, it was found that vaspin had mediator effect between visceral fat and fat mass associations with RMR in obese participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 51 publications
0
22
1
1
Order By: Relevance
“…Youn et al also found that patients with obesity or abnormal insulin sensitivity had elevated serum vaspin levels [19]. Additionally, the serum vaspin concentration in obese patients was higher than that in nonobese patients in the same research [17]. Salama et al (2015) found that vaspin levels are increased in obese children and identified correlations between vaspin concentration and WHR; however, they concluded that vaspin was a less sensitive indicator of abdominal obesity and insulin resistance in obese children compared with visfatin [20].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Youn et al also found that patients with obesity or abnormal insulin sensitivity had elevated serum vaspin levels [19]. Additionally, the serum vaspin concentration in obese patients was higher than that in nonobese patients in the same research [17]. Salama et al (2015) found that vaspin levels are increased in obese children and identified correlations between vaspin concentration and WHR; however, they concluded that vaspin was a less sensitive indicator of abdominal obesity and insulin resistance in obese children compared with visfatin [20].…”
Section: Discussionmentioning
confidence: 95%
“…Also, changes in visceral fat are associated with concomitant changes in glucose tolerance and insulin resistance [16]. It was reported that central adiposity bestows enhanced risk of metabolic complications as compared with peripheral adiposity [17]. Previous study has found that vaspin may improve the metabolism of glucose and decrease glucose concentration [18].…”
Section: Discussionmentioning
confidence: 99%
“…Complete body composition analysis was explained previously [24]. Body composition analyzer BC-418MA-Tanita (United Kingdom) was used to calculate the participant’s body composition [25] including weight, fat mass, fat-free mass, body fat percentage, muscle mass, visceral fat mass, abdominal fat mass. Total body water basis of data were obtained by dual energy X-ray absorptiometry using Bioelectrical Impedance Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D supplementation had no significant effect on vaspin levels, however, a cross sectional study indicated that serum vaspin and vitamin D have negative correlation (Zorlu et al, ). We could not find any clinical trials in the literature evaluating the effect of vitamin D treatment on vaspin concentrations (Moradi, Mirzaei, Abdurahman, Keshavarz, & Hossein‐nezhad, ).…”
Section: Discussionmentioning
confidence: 98%